Simulation Analysis and Experimental Research on Vibration Characteristic of Roller Brush Gearbox of Intelligent Sweeper - Jing Li; Hongbin Yang; Jihua Ren; Aijun Xu (Jixie chuandong)
Aiming at the problem of excessive noise in the gearbox of a certain sweeper， a gearbox dynamics model is established in the multi-body dynamics software RecurDyn， the dynamic meshing force of the gear pair under steady-state conditions is obtained， and the effect of the meshing force on the box body is analyzed. By using the Ansys， the analysis of the modal and dynamic response of the box is carried out， it shows that the peak vibration response is mainly concentrated at the fundamental frequency， double frequency， and double frequency of the gear meshing frequency， which arouses the resonance noise with the gear pair. In order to avoid the resonance zone， a scheme for optimizing the geometric parameters of the gear and improving the structure of the motor assembly is proposed without increasing the box space， and the optimization scheme is tested for noise. The results show that the combination scheme of optimizing gear geometric parameters and reinforcing the motor assembly is the best scheme， and the noise of the whole machine is reduced by about 8.9 dB. It has certain research significance and reference value for the optimization design and vibration and noise reduction of this type of product.